THE USE OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) METHOD TO IMPROVES WRITING SKILLS - Destri Yulandari, Naurah; Mukrim, Mukrim; Rita, Ferry; Budi, Budi (e-Journal of ELTS (English Language Teaching Society), 2023)
The objective of this research is to find out whether the use of the Cooperative Integrated Reading and Composition (CIRC) method of the eleventh-grade students of SMA Negeri 7 Palu can improve the students' writing skills or not; the researchers applied a quasi-experimental design which involved experimental class and control class. The population of this research was the eleventh-grade students at SMA Negeri 7 Palu. The researchers selected the sample by using a purposive sampling technique. The sample of this research was the students of XI 3(experimental class) and XI 1 (control class), which were both classes consisting of 32 students. The technique of data collection was tested (pre-test and post-test). The experimental class was treated by applying the CIRC method, while the method did not use by the control class. The result of the data analysis showed that there was a significant difference between the pre-test and post-test. The researchers found a significant difference between the results of the experimental class. It was proved by applying the testing hypothesis. The researchers found that the t-counted (3.29) was higher than the t-table (2.001). It means that the hypothesis was accepted. In conclusion, using the CIRC method effectively improves the writing skills of the eleventh-grade students of SMA Negeri 7 Palu.